Effects of muscle fatigue induced by countermovement jumps on eficacy parameters of instep ball kicking in soccer - Torreblanca-Martinez, V.; Otero-Saborido, F. M.; Gonzalez-Jurado, J. A. (Journal of Applied Biomechanics, 2017)
The purpose was to study the effects of muscle fatigue induced by countermovement jumps (CMJ) on instep kick foot velocity in young male soccer players. Fifteen under-18 soccer players from a professional club performed maximal velocity instep kicks before and after a fatigue protocol that consisted of continuous CMJ. Foot velocity at impact without fatigue, foot velocity at impact with fatigue, CMJ height without fatigue, maximum jump height in fatigue test, and CMJ height change in fatigue test on a dynamometric platform were measured. There was a significant difference between jump height with and without fatigue (P = .00; ES = 0.8), but there were no significant differences between kicking with fatigue and without fatigue (P = .580, ES = 0.10). In conclusion, although the protocol was intense enough to generate fatigue in the muscles involved in CMJ, there were no significant differences in kicking velocity under fatigue conditions with respect to kicking without fatigue in the soccer players studied. ABSTRACT FROM AUTHOR